Protecting Indigenous Collective Land Property in Indonesia under International Human Rights Norms - Chairul Fahmi; Muhammad Siddiq Armia (Journal of Southeast Asian Human Rights, 2022)
This essay examines the applicability of international human rights instruments as the legal basis to protect indigenous rights to land, territories, and natural resources to non-ratification countries of the Convention on indigenous peoples’ rights, especially to the Indonesian context. In the last few decades, the United Nations has developed and recognized the rights of indigenous peoples, including rights to their ancestral lands, territories, and resources. These rights have been stipulated in several instruments, such as the ILO Conventions No.169 and UNDRIP. Nevertheless, most Asian and African countries have not ratified the Treaty, including Indonesia. Consequently, the rights failed to be adopted into national policies, which the ratification is a pre-condition before came into force through the national regulations. Indonesia also doubted the exclusive rights of land, territories, and resources traditionally owned by indigenous peoples. Legally, lands, territories, and resources are controlled by the States, as mentioned in Article 33 of the 1945 Constitutional law. Economically, Indonesia relies on land, territories, and natural resources to boost its national revenues. To achieve this aim, the expropriation of indigenous land and territories often occurs through land concession policy for private or state-owned companies. As a result, land tenure and social conflict were common phenomena from the New Order Regime until the current day. This conflict spreads across the country from the west part (Sumatra) to the east of Indonesia (Papua). Therefore, author argues that applying general international human rights instruments will be an alternative approach in protecting the fundamental rights related to their traditional land rights in the Indonesian context.